2018
DOI: 10.1186/s12943-018-0813-1
|View full text |Cite
|
Sign up to set email alerts
|

The HNF1α-regulated lncRNA HNF1A-AS1 reverses the malignancy of hepatocellular carcinoma by enhancing the phosphatase activity of SHP-1

Abstract: BackgroundOur previous study has demonstrated that hepatocyte nuclear factor 1α (HNF1α) exerts potent therapeutic effects on hepatocellular carcinoma (HCC). However, the molecular mechanisms by which HNF1α reverses HCC malignancy need to be further elucidated.MethodslncRNA microarray was performed to identify the long noncoding RNAs (lncRNAs) regulated by HNF1α. Chromatin immunoprecipitation and luciferase reporter assays were applied to clarify the mechanism of the transcriptional regulation of HNF1α to HNF1A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
47
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(51 citation statements)
references
References 47 publications
1
47
0
Order By: Relevance
“…It has been shown that the expression of HFN‐1α is associated with cancer risk in several tumors, including hepatocellular and pancreatic carcinoma, renal cancer, ovarian cancer, endometrial cancer, and prostate cancer . However, recent studies also reported the antitumor potentials of HFN‐1α . At this juncture, it is not clear whether the downregulation of HFN‐1α observed in this study is responsible for apoptosis induction and hence, further studies are warranted on these lines.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…It has been shown that the expression of HFN‐1α is associated with cancer risk in several tumors, including hepatocellular and pancreatic carcinoma, renal cancer, ovarian cancer, endometrial cancer, and prostate cancer . However, recent studies also reported the antitumor potentials of HFN‐1α . At this juncture, it is not clear whether the downregulation of HFN‐1α observed in this study is responsible for apoptosis induction and hence, further studies are warranted on these lines.…”
Section: Discussionmentioning
confidence: 65%
“…29,30 However, recent studies also reported the antitumor potentials of HFN-1α. 31,32 At this juncture, it is not clear whether the downregulation of HFN-1α observed in this study is responsible for apoptosis induction and hence, further studies are warranted on these lines.…”
Section: Discussionmentioning
confidence: 85%
“…Mechanistically, HNF1a-AS1 may function as a competing endogenous RNA to repress miRNA-mediated post-transcriptional regulation in cancer progression (Fang et al, 2017). Transcriptional regulation of HNF1a-AS1 by HNF1a has also been reported in hepatocellular carcinoma (Ding et al, 2018). HNF1a-AS1 was further shown to directly bind to the C terminus of Scr homology region 2 domain-containing phosphatase 1 and increase the phosphatase activity of this protein, which can reverse the malignancy of hepatocellular carcinoma (Ding et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…A recent study revealed that lncRNA TSLNC8 (also known as LINC00589) exerts its tumor suppressive activity through the inactivation of the IL-6/STAT3 signaling pathway via physically interacting with TKT and STAT3, and thus inhibiting STAT3 phosphorylation and transcriptional activity in HCC [36]. Another study indicated that lncRNA HNF1A-AS1 (HNF1A antisense RNA 1) can inhibit the growth and metastasis of HCC by activating phosphatase through direct binding with the C-terminal of SHP-1 (SH2-containing protein tyrosine phosphatase-1) [30]. However, the effect of lncRNAs on gene expression through protein modification is not limited to the phosphorylation of target proteins.…”
Section: Protein Modificationsmentioning
confidence: 99%